2014
DOI: 10.1093/ije/dyu202
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of metachronous contralateral breast cancer in Denmark 1978–2009

Abstract: Occurrence of cancer in the contralateral breast seems to be rather independent of time passed since the first primary. The finding of a decreasing incidence of CBC after 1997 is likely to be due to more women receiving systemic adjuvant therapy such as tamoxifen and longer duration of this treatment as well as the introduction of aromatase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
2
32
1
Order By: Relevance
“…Rasmussen et al . reported 10‐year cumulative metachronous CBC risks of approximately 4–5.5% in a large population based sample of over 85.000 women with previous invasive BC without distant metastases in Denmark . A population‐based study performed in Switzerland revealed a CBC incidence rate of approximately 4.5–5 per 1,000 PY after 4–11 years follow‐up, compared to 4.1 per 1.000 PY in our study after 5–10 years follow‐up .…”
Section: Discussioncontrasting
confidence: 63%
“…Rasmussen et al . reported 10‐year cumulative metachronous CBC risks of approximately 4–5.5% in a large population based sample of over 85.000 women with previous invasive BC without distant metastases in Denmark . A population‐based study performed in Switzerland revealed a CBC incidence rate of approximately 4.5–5 per 1,000 PY after 4–11 years follow‐up, compared to 4.1 per 1.000 PY in our study after 5–10 years follow‐up .…”
Section: Discussioncontrasting
confidence: 63%
“…The Danish study referred to above exhibited an increasing incidence in younger patients with a peak 2-4 years after diagnosis, but when adjusted for age and calendar period, incidence rates where more or less constant over time (Rasmussen et al 2014). We are not able to investigate the influence of age on the time to incidence of CBC, as our number of cases is too small for examining incidence rates for certain age groups with regard to follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…Young women might still have an increasing risk of developing a malignant tumour of the breast compared to a declining incidence in general and are probably more likely to develop CBC. A recently published paper with data from the Danish Cancer Registry examined the influence of the longer follow-up of younger patients on the incidence of CBC and also still found a decreasing incidence of CBC with age when limiting the follow-up time (Rasmussen et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…47 Of note, the development of CBC in the Danish registry study was independent of time since a patient’s first cancer across all ages, with steady rates over 10 years of follow-up. 11 …”
Section: Risk Of In-breast Events In Older Breast Cancer Survivorsmentioning
confidence: 99%
“…Further, studies have consistently shown that the risk of second breast cancer events in survivors does not plateau with time, suggesting that there may be continued benefit of mammography indefinitely. 10,11 Explicit guidance on how to approach surveillance in older or frail breast cancer survivors is lacking. Further, the limited data regarding surveillance in older cancer survivors across all cancers is now widely recognized as a significant research gap and priority.…”
Section: Introductionmentioning
confidence: 99%